Marek's Disease in Chicken: I. Aetiology, Pathogenesis and its Control - R M A Adjid; R Damayanti; H Hamid; T Sjafriati; Darminto . (Indonesian Center for Animal Research and Development, 2002)
Marek’s disease (MD) is a neoplastic and neuropathic disease of poultry, especially chicken, caused by a highly contagious cell-associated herpesvirus. Marek’s disease is one of poultry diseases that is seriously concerned by poultry farmers. Before introduction of vaccine technology, the disease caused great economic loss in poultry industry, for example, in the United State the annual losses was estimated around 150 millions. Marek’s disease virus is relatively resistant to physical and chemical influence. In poultry farms the virus remains infectious for months and play an important role as source of infection. Pathogenesis of the disease is complex and influenced by factors. There are four phases of infection: early cytolytic infection, latent infection, second phase of cytolytic infection, and proliferative infection. Pathogenesis influenced by factors causes variety on clinical syndroms and incubation period of the disease in field condition. Successful disease control can be achieved, with vaccination as the main program, by selection of breed resistance and good management systems. The emergence of more virulent pathotypes of MD is a serious threat to the poultry industry, which requires development of more effective control strategies. Key words. Marek, poultry, etiology, pathogenesis, control